La valutazione per il governo dell'Università - Pasquale Basilicata (LED Edizioni Universitarie, 2010)
Evaluation for University Governance The article reflects on how evaluation is essential for university governance in an advanced model of autonomy. Assuming there is no autonomy without responsibility, and no responsibility without evaluation of results, a new conception of evaluation of quality is provided, going beyond the two traditional ones, i.e. evaluation conducted by academia, and procedural quality based on compulsory standards. Scientific institutions must account for their powers, results and resources used, according to criteria that are as objective, predefined, clear and «verifiable» as possible. Only this kind of evaluation can achieve three fundamental aims: making universities responsible towards the state and society; developing virtuous competitive attitudes for university effectiveness and efficiency; rationalising public expenditure in higher education. The article then examines the background to the Bologna Process and the recent regulation of ANVUR (National University and Research Evaluation Agency) by Italian political institutions that have finally grasped the urgency of an external monitoring and coordination body to overcome the fragmentation of evaluation hitherto conducted with different actors, methods, aims and targets, involving great communication difficulties between national and international evaluation bodies. The need for quantitative indicators as well as peer-reviews in research quality evaluation is emphasised. Moreover, since governance cannot be separated from state allocation of resources to universities, the state university financing model (Education Ministry decree of 28 July 2004) is illustrated which led to overcoming old funding criteria largely independent of service quality. Finally, a critical analysis is made of evaluation in Italy and the current problems in funding.